2016
DOI: 10.1038/srep31158
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Induces Excitotoxicity Mediated by APC/C-Cdh1 Depletion That Can Be Prevented by Glutaminase Inhibition Promoting Neuronal Survival

Abstract: The E3 ubiquitin ligase anaphase-promoting complex/cyclosome (APC/C) is activated by the fizzy-related protein homolog/CDC20-like protein 1 (cdh1) in post-mitotic neurons. Growing evidence suggests that dysregulation of APC/C-Cdh1 is involved in neurodegenerative diseases. Here we show in neurons that oligomers of amyloid beta (Aβ), a peptide related to Alzheimer’s disease, cause proteasome-dependent degradation of cdh1. This leads to a subsequent increase in glutaminase (a degradation target of APC/C-Cdh1), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 48 publications
2
45
0
2
Order By: Relevance
“…Interestingly, growing evidence suggests that dysregulation of APC/C-Cdh1 is involved in neurodegenerative diseases, potentially as a consequence of amyloid-ß driven proteasome-dependent degradation of CDH1 [50]. On the other hand, significantly higher methylation level of CDH1, inducing its inactivation, plays an important role in lung cancer [51].…”
Section: New Biological Insights On the Inverse Comorbidity Between Amentioning
confidence: 99%
“…Interestingly, growing evidence suggests that dysregulation of APC/C-Cdh1 is involved in neurodegenerative diseases, potentially as a consequence of amyloid-ß driven proteasome-dependent degradation of CDH1 [50]. On the other hand, significantly higher methylation level of CDH1, inducing its inactivation, plays an important role in lung cancer [51].…”
Section: New Biological Insights On the Inverse Comorbidity Between Amentioning
confidence: 99%
“…More interesting is that Aβ inhibits cdh-1, depresses APC activity inducing rising levels of glutaminase and increases glutamate levels expressing thus exicitotoxicity in AD. This mediated excitotoxicity was found to be regulated through Cdh-1 [48]. Cdh 1 is primarily in a non phosphyrated form found in the nucleus.…”
Section: +mentioning
confidence: 99%
“…Recent finding by T. Fuchsberger [48] that Aβ with APC/C mediates excitotoxicity through the glutaminase pathway showed that this protein not only exerts properties for the late phases of the cell cycle but also properties for the maintenance of the postmitotic state through repressing cyclin B activity which suggest that APC/C has an important role in the pathogenesis of Alzheimer's disease. Glutamate is the most abundant neurotransmitter in the brain, with a wide range of functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported recently that Aβ causes a proteasome-dependent degradation of cdh1 [21], suggesting its involvement in Alzheimer’s disease (AD).…”
Section: Introductionmentioning
confidence: 99%